Reconstructing Islamic Economic Methodology Through an Interdisciplinary Integrative Approach - Rika Widianita; Nunu Burhanuddin (Imara: Jurnal Riset Ekonomi Islam, 2026)
Background. Global economic dynamics such as financial digitalization, economic inequality, climate change, and technological disruption have given rise to new methodological needs that are capable of integrating sharia values with modern economic theory and contemporary scientific tools to respond to global challenges. Purpose. This study aims to reconstruct Islamic economic methodology through an integrative interdisciplinary approach so that this discipline can comprehensively address the epistemological, methodological, and empirical challenges of contemporary economics. Method. This study uses a qualitative method with a literature review design. This approach was chosen because the focus of the study is to analyze the concepts, critiques, and reconstruction of Islamic economic methodology based on theory, scientific literature, and the latest research results. Results. The findings show that Islamic economics can only develop as a modern scientific discipline if it is able to integrate normative, empirical, interdisciplinary, and systemic approaches into its methodological framework.  Conclusion. The findings show that Islamic economics is in a phase of integrative reconstruction, where the fragmentation of classical methodology is no longer adequate to answer modern economic issues. Therefore, reconstruction must be based on the integration of sharia values with modern scientific methods through the integration of various sciences and systems.